Drug Susceptibility Patterns in MDR-TB Patients: Challenges for Future Regimen Design. A Cross-Sectional Study. - Helen R Stagg; James Brown; Elmira Ibraim; Vija Riekstiņa; Piret Viiklepp; Andra Cīrule; Horia Cocei; Manfred Danilovitš; Gunta Dravniece; Charlotte Jackson; Peter J White (PLoS ONE)
Globally, there is substantial concern regarding the challenges of treating complex drug resistance patterns in multidrug resistant tuberculosis cases. Utilising data from three different settings (Estonia, Latvia, Romania) we sought to contrast drug susceptibility profiles for multidrug resistant tuberculosis cases, highlight the difficulties in designing universal regimen, and inform future regimen selection. Demographic and microbiological surveillance data for multidrug resistant tuberculosis cases from 2004-13 were analysed. High levels of additional resistance to currently recommended second line drugs were seen in all settings, with extensive variability between countries. Accurate drug susceptibility testing and drug susceptibility testing data are vital to inform the development of comprehensive, flexible, multidrug resistant tuberculosis guidance.